Koefoed et al., Antarctic ordinary chondrite K isotope and major elemental data ... - Koefoed, Piers (Mendeley Data, 2024)
K isotope and major elemental data for the four Antarctic unequilibrated ordinary chondrites analyzed in the Koefoed et al. study. The data show the chondrules from these ordinary chondrites all exhibit light K isotope compositions, suggesting incomplete condensation as a formation mechanism. ...